(untitled) (Research, Society and Development, 2021)
Neuropsychology is a considerably new field of activity in face of the normalization of psychology in Brazil in its 59 years. Since, the practice of neuropsychologist has been shown to be essential with the multi and interdisciplinary team in the process of assessment and rehabilitation of children with autism spectrum disorder. This study will present the role of the neuropsychologist in the care and rehabilitation of children with ASD. This is a semi-structured qualitative interview conducted with two neuropsychologists, using Bardin’s content analysis to describe the results. It was observed that the neuropsychologist helps in the initial stories, in addition to providing assistance to the team and family members on the management that should be adopted in the patient’s rehabilitation, although difficulties are specified in team practice, however, acting in group is required for full diagnosis and rehabilitation. Therefore, the neuropsychologist has become a professional present in the rehabilitation teams of children with ASD, singing in hospitals as well as in specialized centers, considering that, with their knowledge, the development process gains quality and practicality during the treatment.